Protocol for the United Kingdom Rotator CuffStudy (UKUFF): a randomised controlled trial of open and arthroscopic rotatorcuff repair. Issue 5 (May 2014) - Carr, A. J.; Rees, J. L.; Ramsay, C. R.; Fitzpatrick, R.; Gray, A.; Moser, J.; Dawson, J.; Bruhn, H.; Cooper, C. D.; Beard, D. J.; Campbell, M. K.
Abstract : This protocol describes a pragmatic multicentre randomised controlled trial (RCT) to assess the clinical and cost effectiveness of arthroscopic and open surgery in the management of rotator cuff tears. This trial began in 2007 and was modified in 2010, with the removal of a non-operative arm due to high rates of early crossover to surgery. Cite this article: Bone Joint Res 2014;3:155–60.